THE IMPACT OF INTANGIBLE ASSETS ON FINANCIAL PERFORMANCE : THE MODERATING ROLE OF AUDIT STATUS IN LISTED SPORTS CLUBS WORLDWIDE - Herbert, Go George; Magdalena, Renna; Wijaya, Chavella Janice Davalin; Emanuel, Christian (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This research investigates the impact of intangible assets within the context of the financial performance of the sports clubs quoted on the stock market worldwide, focusing on the moderating effect of the audit status. Concerning financial performance, this study uses Tobin's Q. It assesses whether or not intangible assets that include brand equity, fan bases, control over players, and ownership of media rights are relevant for increasing the value of the market and the stability of the club. Reviewing a sample of 310 data of sports clubs covering a period of 2014 to 2023, the study introduces the audit status as a moderating variable, postulating that it is likely that high audit status will increase the validity of firm financial report information. The research results show a significant positive impact between intangible assets and firm financial performance. Besides, audit status moderated this relationship, whereby clubs with higher audit status achieved better financial performance due to raised audit integrity and investor prerequisite greater transparency. These findings emphasize the importance of intangible assets and audit status in improving the financial performance of the sports clubs and provide a better understanding of the management, the investors, and the auditors in the sports industry.